2021
DOI: 10.1021/acsomega.1c04030
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Organosolv and Alkaline Pretreatment: An Efficient Approach toward the Production of Cellulose from Rice Straw

Abstract: The efficient removal of silica from rice straw and separation of its major components is essential for further valorization to produce value-added products. With regard to this, the isolation of cellulose (CEL), hemicellulose (HEM), and lignin (LIG) is imperative but quite challenging. Among several pretreatments of lignocellulosic biomass, the organosolv approach is deemed as one of the promising methods. Here, we present two different two-step approaches for the removal of silica and disintegration of signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Hemicellulose is a susceptible component of RS for acid and alkali pretreatment because it solubilises in alkali. Aggarwal et al 20 recently reported using organosolv and alkaline pretreatment of RS for cellulose production with about 82% total removal of hemicellulose and lignin along with 90.4% of silica removal from RS. It was noted that % lignin removal was higher for A (9.2%) as compared to D (0.54%), % extractives removal was lower for A and no change was reported for D. Quick lime used during preparation of petha sweet, resulted in increase of ash content due to absorption of Ca 2+ ions in A 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Hemicellulose is a susceptible component of RS for acid and alkali pretreatment because it solubilises in alkali. Aggarwal et al 20 recently reported using organosolv and alkaline pretreatment of RS for cellulose production with about 82% total removal of hemicellulose and lignin along with 90.4% of silica removal from RS. It was noted that % lignin removal was higher for A (9.2%) as compared to D (0.54%), % extractives removal was lower for A and no change was reported for D. Quick lime used during preparation of petha sweet, resulted in increase of ash content due to absorption of Ca 2+ ions in A 15 .…”
Section: Resultsmentioning
confidence: 99%
“…29,30 However, high-value chemicals and biomaterials can also be obtained. The main studies focus on generating cellulose nanofibrils (CNF), 31 nanocellulose, 32 cellulose nanocrystals (CNCs), 33,34 butyl glucosides, 35 carboxymethylcellulose 36 and dissolving pulp. 37…”
Section: Cellulosementioning
confidence: 99%
“…3 Of these, organosolv pretreatment is an emerging approach to obtain high-quality lignin and high-purity cellulose. 4,5 In the context of promoting an eco-friendly and sustainable bioeconomy and to realize the clean separation and high value-added utilization of lignocellulosic biomass, 6 as alternatives to conventional organic solvents, bio-based green solvents are being investigated, such as γ-valerolactone (GVL), 7 dihydrolevoglucosenone (Cyrene) 8 and dimethyl isosorbide (DMI). 1 Among these, DMI is abio-derived, aprotic, high boiling point, and non-toxic solvent which can be produced from d -glucose.…”
Section: Introductionmentioning
confidence: 99%